Finite-Time Orbit Control for Spacecraft Formation with External Disturbances and Limited Data Communication - Lei Xing; Dechao Ran; Jian Zhang; Li Huang (International Journal of Aerospace Engineering)
This work addresses the finite-time orbit control problem for spacecraft formation flying with external disturbances and limited data communication. A hysteretic quantizer is employed for data quantization in the controller-actuator channel to decrease the communication rate and prevent the chattering phenomenon caused by the logarithmic quantizer. Combined with the adding one power integrator method and backstepping technique, a new finite-time tracking control strategy with adaptation law is designed to ensure that the closed-loop system is practical finite-time stable, and that the tracking errors of relative position and velocity are bounded within finite-time despite with limited data communication and external disturbances. Finally, an example is shown to validate the effectiveness of the proposed finite-time tracking controller.